Minimun distance from the body of water to the miners components - Atarama, Eduardo (2014)
Assessors at General Management of Mining Environmental Affairs of the Ministry of Energy and Mines have as an evaluation criterion in environmental impact assessment of mineral exploration that any platform or component must not to be to less than 50 meters of a water body. Otherwise, they don’t approve the project. But, what technical support this common criterion is based? Is it a test that finds no technical basis to excuse his decisions about the evaluation of any environmental study? Or is it a copy of any law in a neighboring country? Water is a vital resource for mining exploration activities, so we must to evaluate carefully how much is it affected during this activity. I think that it is necessary to revalue and propose two or more minimal distances according to the experience and research realized. Let’s not allow that a criterion be imposed when not necessarily it will be the correct procedure in the practice. But always thinking that the priority is to monitor and preserve such and important resource for everyone as water.